Evaluation of Carbon thin Films Using Raman Spectroscopy - Silva,Danilo Lopes Costa e (2018)
Carbon thin films deposited by the magnetron sputtering technique were evaluated by Raman spectroscopy to study the influence on their crystallinity caused by different parameters like the carbon deposition time, the different buffer-layers and substrates employed and also two distinct heat treatments. The present results showed that the choice of these parameters plays an important role in the production of these films. The results also indicate the possibility of using the technique for the production of carbon thin films to be employed in future in applications with controlled content of structural defects, predominance of ordered sp2 bondings and tendency of graphitization.